Vänersjöfartens miljönytta? - En studie av miljöeffekterna av inlandssjöfarten i Västsverige - Grauers, Henning; Persson, Elias (My University, 2016)
The purpose of this thesis is to examine the environmental impact from the shipping on River Göta Älv and Lake Vänern in Western Sweden in various future scenarios. The outline of the thesis is the many changed circumstances for this type of shipping in Western Sweden, both beneficial and negative, that have occurred in recent years. The study aims to identify what environmental impacts, comprised of emissions to air (Carbon Dioxide, Sulphur Oxides, Nitrogen Oxides and Particulate Matter) that a fully developed, as opposed to discontinued, shipping on Lake Vänern may cause. This is conducted by comparing the emissions from the present shipping as well as estimated emissions of the future shipping (as of year 2030) with a scenario where the transport work is performed by trucks. Furthermore, factors that are estimated to affect the development of the shipping in the region are examined. By conducting an archive analysis, a number of factors that can affect the future scenarios have been identified. These factors primarily consist of infrastructural barriers, such as bridges and locks. By using calculation tools from the Network of Transport and Environment (NTM), the results show that inland shipping is an energy efficient mode of transport. However, this mode of transport leads to high emissions of air pollutants compared to road traffic.
Keywords: Transport; Transportteknik och logistik; Transport; Transport Systems and Logistics